On the Effect of Ghost Force in the Quasicontinuum Method: Dynamic Problems in One Dimension (Communications in Computational Physics, 2014)
Numerical error caused by "ghost forces" in a quasicontinuum method isstudied in the context of dynamic problems. The error in the discrete W1,∞ norm is analyzed for the time scale $\mathcal{O}$($ε$) and the time scale $\mathcal{O}$(1) with ε being the lattice spacing.